'Wisdom' and the Gender Fallacy - Turner, Geoffrey (The expository times, 2009)
The ascription of a particular gender to a noun is a convention of a language's grammar and normally has nothing to do with the substance or character of the thing signified. Native English-speakers often do not appreciate this as few nouns in English have gender. The gender fallacy of ascribing masculine or feminine characteristics to things on the basis of their gender in grammar is a particular problem in biblical scholarship, especially with 'wisdom' and 'spirit' and the implication for the Christian understanding of God as Trinity. Some examples of bad arguments developing from this fallacy are offered, as well as a few examples of authors who have appreciated the fallacy.